2010
DOI: 10.1158/0008-5472.sabcs10-s3-3
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S3-3: First Results of the NeoALTTO Trial (BIG 01-06/EGF 106903): A Phase III, Randomized, Open Label, Neoadjuvant Study of Lapatinib, Trastuzumab, and Their Combination Plus Paclitaxel in Women with HER2-Positive Primary Breast Cancer

Abstract: Background: The addition of trastuzumab to neoadjuvant chemotherapy has significantly improved pathological complete response (pCR) in patients with HER2-positive early breast cancer (BC). Lapatinib, a dual HER2/EGFR tyrosine kinase inhibitor, combined with chemotherapy has significantly improved progression free survival in patients with metastatic HER2-positive BC. Additionally, lapatinib combined with trastuzumab improved disease-free and overall survival in patients with metastatic HER2-positive BC. The Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
5

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 0 publications
5
55
0
5
Order By: Relevance
“…11 More recently, increased incidence and severity of diarrhea has also been observed when lapatinib is combined with taxane chemotherapy, leading to a need for dose reduction in this setting. 12 Current favored theories for the underlying pathology were not significantly different to control animals ( Fig. S1).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…11 More recently, increased incidence and severity of diarrhea has also been observed when lapatinib is combined with taxane chemotherapy, leading to a need for dose reduction in this setting. 12 Current favored theories for the underlying pathology were not significantly different to control animals ( Fig. S1).…”
Section: Introductionmentioning
confidence: 88%
“…15,16 Inhibition of HER2 alone with trastuzumab has not been associated with as frequent gastrointestinal toxicities clinically, 12 which may be due to mode of delivery (intravenous vs. oral) or indicate that EGFR blockage, rather than HER2 blockade, is primarily responsible for intestinal dysfunction. However, further in vivo experiments are required to develop these hypotheses and to gain a better understanding of lapatinib-specific intestinal changes and effects on drug absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lapatinib as monotherapy and in combination with paclitaxel has clinical activity as first-line treatment in HER2-positive patients with breast cancer (9,10). Recently, our group and others reported that combinations of anti-HER2 agents with nonoverlapping mechanisms of action, so-called dual HER2 blockade, is superior to treatment with single-agent trastuzumab (11)(12)(13)(14) and is active in patients who are resistant to trastuzumab-based therapies (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The NeoSphere trial tested the combination of trastuzumab and pertuzumab AE chemotherapy in the neoadjuvant setting in patients with newly diagnosed HER2-positive breast cancer (42). Likewise, the concept of dual HER2 blockade with trastuzumab and the TKI lapatinib was also successfully explored in a neoadjuvant randomized phase III study (43). These study designs are suited for obtaining onstudy tumor biopsies.…”
Section: Clinical Approachesmentioning
confidence: 99%